Immunoglobulin and T Cell Receptor Genes: IMGT® and the Birth and Rise of Immunoinformatics - Lefranc, Marie-Paule (Frontiers in Immunology, 2014)
IMGT®, the international ImMunoGeneTics information system®, http://www.imgt.org (CNRS and Université Montpellier 2) is the global reference in immunogenetics and immunoinformatics. By its creation in 1989, IMGT® marked the advent of immunoinformatics, which emerged at the interface between immunogenetics and bioinformatics. IMGT® is specialized in the immunoglobulins (IG) or antibodies, T cell receptors (TR), major histocompatibility (MH), and proteins of the IgSF and MhSF superfamilies. IMGT® has been built on the IMGT-ONTOLOGY axioms and concepts, which bridged the gap between genes, sequences and three-dimensional (3D) structures. The concepts include the IMGT® standardized keywords (concepts of identification), IMGT® standardized labels (concepts of description), IMGT® standardized nomenclature (concepts of classification), IMGT unique numbering and IMGT Colliers de Perles (concepts of numerotation). IMGT® comprises 7 databases, 15,000 pages of web resources and 17 tools, and provides a high-quality and integrated system for the analysis of the genomic and expressed IG and TR repertoire of the adaptive immune responses. Tools and databases are used in basic, veterinary and medical research, in clinical applications (mutation analysis in leukemia and lymphoma) and in antibody engineering and humanization. They include, as examples: IMGT/V-QUEST and IMGT/JunctionAnalysis for nucleotide sequence analysis and their high-throughput version IMGT/HighV-QUEST for next generation sequencing (500,000 sequences per batch), IMGT/DomainGapAlign for amino acid sequence analysis of IG and TR variable and constant domains and of MH groove domains, IMGT/3Dstructure-DB for 3D structures, contact analysis and paratope/epitope interactions of IG/antigen and TR/peptide-MH complexes and IMGT/mAb-DB interface for therapeutic antibodies and fusion proteins for immunological applications (FPIA).